The Relationship between Sleep Quality, Cyberbullying, and Internet Addiction in Adolescents - Septianawati, Paramita; Mustikawati, Irma Finurina; Kusuma, Inggar Ratna; Pratama, Tisna Sendy (Smart Medical Journal, 2025)
Background: Teenagers use the internet for their daily needs such as attending online classes, watching entertainment (such as YouTube or playing games) or even playing social media. The purpose of this study was to determine the relationship between cyberbullying incidents and sleep quality with internet addiction in adolescents.Research Methods: This study used an observational analytical method using the PSQI, KDAI, and cyberbullying questionnaires. 276 adolescent respondents who were willing to fill out the questionnaire distributed via G-form were obtained. This study was analyzed with SPSS 26.0.Results :The univariate results showed that 75 (27.2%) adolescents were addicted to the internet, 82 (29.7%) adolescents had been victims/perpetrators of cyberbullying, respondents experienced overall sleep quality, 90 students (32.6%) had good sleep quality and 186 students (67.4%) had poor sleep quality. The results of the bivariate analysis of this study found a significant relationship between internet-addicted teenagers and cyberbullying perpetrators (p = 0.000). A significant relationship was found between cyberbullying victims and internet addiction (p = 0.028). There was a significant relationship between subjective sleep quality (p = 0.000), sleep latency (p = 0.022), and sleep disturbance (p = 0.032) with internet addiction (p <0.05). The results of the Chi-Square statistical test obtained a value of 0.031, there was also a significant relationship between overall sleep quality and internet addiction. Using logistic regression, it can be seen that the independent variables that have a sig. <0.05 are the cyberbullying perpetrator variables and subjective sleep quality, so it can be said that both independent variables have a significant effect on internet addiction.Conclusion: Significant relationship between subjective sleep quality and cyberbullying perpetrators on teenagers who tend to be addicted to the internet.